1997
DOI: 10.1111/j.1600-079x.1997.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin's antioxidant protection against δ‐aminolevulinic acid‐induced oxidative damage in rat cerebellum

Abstract: delta-aminolevulinic acid (ALA) promotes the generation of reactive oxygen species (ROS). Accumulation of ALA, as occurs in acute intermittent porphyria (AIP), is a potential endogenous source of ROS, which can then exert oxidative damage to cell structures. In this work we investigated the role of pharmacological concentrations of melatonin on the deleterious effect of ALA and its effect on porphyrin biosynthesis. Rat cerebellum incubations were carried out with either ALA (1.0 mM) together with increasing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 35 publications
6
25
0
1
Order By: Relevance
“…Taking into account the fact that oxidative stress is a condition referred to as an imbalance between oxidant generation and antioxidant defense systems, which GSH is a leading substrate for enzymatic antioxidant functions and it is also a known radical scavenger, its precursor SAM would be acting as an antioxidant. This explanation could also be extended to ALA toxicity, because ALA accumulation generates ROS (Princ et al 1997;1998;Reiter and Tyrrel 2000) and it has been shown that SAM was capable of counteracting this effect (Paredes et al 1987). Our results clearly demonstrated that in all tissues of Cd 2+ treated plants there is accumulation of ALA as well as diminution of PBG content as a result of ALA-D activity inhibition.…”
Section: Discussionsupporting
confidence: 49%
“…Taking into account the fact that oxidative stress is a condition referred to as an imbalance between oxidant generation and antioxidant defense systems, which GSH is a leading substrate for enzymatic antioxidant functions and it is also a known radical scavenger, its precursor SAM would be acting as an antioxidant. This explanation could also be extended to ALA toxicity, because ALA accumulation generates ROS (Princ et al 1997;1998;Reiter and Tyrrel 2000) and it has been shown that SAM was capable of counteracting this effect (Paredes et al 1987). Our results clearly demonstrated that in all tissues of Cd 2+ treated plants there is accumulation of ALA as well as diminution of PBG content as a result of ALA-D activity inhibition.…”
Section: Discussionsupporting
confidence: 49%
“…The cerebellum, which is a target of melatonin G-protein coupled receptors [37]–[40], was used as a classical model to study the protective effect of melatonin against hyperbaric oxygen exposure [41], lipid peroxidation [42], [43], glutamate-induced neurotoxicity [44], aluminum exposition [45] and hypoxia [46]. Melatonin was shown to interfere with cerebellar tissue by inhibiting glutamate release [47], the transient outward flow of potassium [48], nicotinic currents [49] and the migration of granule cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…To name only a few, melatonin has been successfully used to reduce neural damage during drug-induced excitotoxicity [182], models of Alzheimer's disease [183], models of Parkinson's disease, [184] nitric oxide neurotoxicity and ischemia-reperfusion injury [185], acute intermittent porphyria [186], lipopolysaccharide exposure [187], and hyperbaric oxygen exposure [188]. In peripheral organs as well, melatonin has proven highly effective in combatting cellular and tissue damage due to oxidative stress [170,171,174,189,190].…”
Section: The Utility Of Melatonin As a Pharmacological Agent In Oxidamentioning
confidence: 99%